Considerações sobre o Ideb: propostas e desafios para uma educação de qualidade na rede municipal de ensino do município de Telêmaco Borba/PR - Machado, Gilmar Nunes (2011)
This research presents an approach about the implantation of Development Index of Basic Education – “IDEB” (Índice de desenvolvimento da Educação básica) - and its relevance to the development of public politics aimed to improving the quality education. The “IDEB” appeared as a result of external evaluations trajectory from the creation of the Development Plan for Basic Education that expose a concern to provide for Brazilian people a quality education. As goal, the research sought to examine the “IDEB” influence from the definition of the indicator term guiding to the public politics and as an instrument of preparation, direction and control of educational activities developed by the Municipal Education Office “(Secretaria Municipal de Educaçao)”. Based on data released by the Education Department “(MEC – Ministério da Educação)” and information given from Telêmaco Borba Municipal Education Office demonstrated the municipal schools performance in the state and microregional context. The results observed denote that the basic education in this city is moving progressively, but the goal of IDEB expected to be achieved until 2022 continue to being a challenge that will require constant work and dedication by all segments related to education.